Shooting short videos in French with mobile phones. - Gabarre, Serge; Gabarre, Cecile (2010)
In Malaysia, the use of French language is virtually nonexistent. Furthermore, students who major in French frequently do not choose this program voluntarily; often it is chosen for them by a national clearing agency. In this context, how can we boost learners’ participation and motivation in a course they have not selected? In a blended approach of e-learning, and m-learning, students were asked to use both the internet and their mobile phones to produce multimedia documents. These resources were then shared and evaluated on an e-learning platform. Evaluations were both self-and peer conducted. During and after this project, quantitative and qualitative data were collected. Our findings reveal that participation and motivation were mutually increased. This was achieved by implicating the students in the learning process, from the conception to the distribution and finally evaluation of resources. As a result, communication skills were boosted and an online community was forged. Could these results have been obtained without the use of technology? It is probable that an activity where messages were pinned on a board could also have enhanced the learning process. However, it seems unlikely that learners would have attained such a rich level of communication without employing ICTs. Mobile phones are important in the learners’ culture and including this technology proved more effective than expected.